Сomparative study of territorial ethnic autonomies - M. Kh. FARUKSHIN; A. R. ZARIPOVA (Сравнительная политика, 2023)
The article discusses the approaches and methods of territorial ethnic autonomies comparative research that are part of both federal and unitary states. The statement on the dual role that these autonomies play is substantiated. The analysis of autonomous communities to assess positive and negative practices is possible only on the basis of comparison. The general features of autonomies are shown depending on the form of government. The influence of the ethnic factor on the autonomy and state institutions is revealed. The research focused on comparative analysis of ethnic autonomies, including the definition of the main comparison options for studying the distribution of power between the autonomy and the state, the selection of indicators that reveal them. The article reveals the possibilities of processing the obtained data for each group of indicators using quantitative and qualitative research methods.